2020
DOI: 10.1515/ijnes-2019-0081
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ engagement and experiences with virtual reality in an undergraduate bioscience course

Abstract: ObjectivesThe challenges of bioscience courses such as anatomy and physiology in nursing education are well documented. Virtual reality has recently become accessible and may support student engagement. The purpose of this project was to describe students’ engagement and experiences with virtual reality in a first-year nursing course on anatomy, physiology, and health assessment.MethodsWe used a cross-sectional design and collected both quantitative and qualitative data. The Exploratory Learning Model guided o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Consistent with the results of other studies, all nursing students found the virtual simulation system as a novel, flexible, and interesting learning tool, which could help them familiarize themselves with the different scenarios encountered in nursing practice [ 41 ]. Virtual simulation systems provide nursing students with a realistic and immersive environment to improve the efficiency of theoretical knowledge transfer, without any barriers of time or space [ 42 ]. In addition, it can provide nursing students with a safe and private operating environment for trial and error.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results of other studies, all nursing students found the virtual simulation system as a novel, flexible, and interesting learning tool, which could help them familiarize themselves with the different scenarios encountered in nursing practice [ 41 ]. Virtual simulation systems provide nursing students with a realistic and immersive environment to improve the efficiency of theoretical knowledge transfer, without any barriers of time or space [ 42 ]. In addition, it can provide nursing students with a safe and private operating environment for trial and error.…”
Section: Discussionmentioning
confidence: 99%
“…Some possible explanations for the benefits might be the result of the “novelty effect,” 27 and the novel nature of VR increased their motivation and made learning more interesting. 28 The use of VR aids is therefore quite feasible and is a potential alternative method for in-person training in the medical field.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual reality offers an immersive experience with inherent benefits for participants (eg, increased immersion, quick adaptation, safe practice, alleviation of anxiety). Some possible explanations for the benefits might be the result of the “novelty effect,” 27 and the novel nature of VR increased their motivation and made learning more interesting 28 . The use of VR aids is therefore quite feasible and is a potential alternative method for in-person training in the medical field.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies required clinical training experience as an inclusion criterion [28,30,47]. However, most studies provided theoretical lectures before implementing the VR intervention [29,31,32,34,35,[42][43][44]46,47,49]. Students perceived their engagement to be higher in VR and found that it was easy to use and helped their learning, and they recommended it.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Furthermore, the model posits that learning depends on the teacher and student interactions, expectations, and roles. [43] Examine the differences in learning outcomes satisfaction and self-confidence based on type of simulation VR or HFS [33] Evaluate the use of VR simulation compared to hybrid simulation as a training modality [32] Provide new evidence in how varying levels of immersion are perceived by nursing students using VRS [44] Evaluate the use of VRS by examining two varying levels of VS on learning outcomes and retention and gain an understanding of the student experience Experiential Learning Theory (ELT) [46] Describe students' experiences with VR on anatomy and health assessment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%